Fostering sustainable development thinking through lean engineering education - Alves, Anabela Carvalho (2015)
An implementation plan for the UN Decade of Education for Sustainable Development (ESD) by the implementing agency UNESCO, launched in 2005 to build partnerships with various partners mainly aimed to reflect the great diversity of interests, concerns, and challenges for ESD. Embedded in this UN program is the challenge to academic engineering programs to develop a technical workforce which is capable of designing and continually developing sustainable processes and products. ESD therefore requires engineers to be able to learn and perform in an interdisciplinary work environment as critical thinkers and problem solvers, to be value-driven and to practice participatory and transparent decision making. Taking these challenges back into curriculum development, the authors of this paper propose that their Lean Engineering Education (LEE) initiative be examined and scrutinized as a contribution to ESD. Thus, this paper reviews ESD roots and partnerships and, then, present, succinctly, LEE as a curricular innovation for engineering courses that promotes the behavior intended for future engineers, to foster a ESD and the Sustainable Development thinking.